Two new species and a new genus of soft scale insects (Hemiptera: Coccomorpha: Coccidae) from the Brazilian Cerrado - Kondo, Takumasa; Silva, Vitor Cezar Pacheco Da; Peronti, Ana Lúcia Benfatti Gonzalez (Zootaxa, 2026)
Two new species of soft scale insect (Hemiptera: Coccomorpha: Coccidae) from the Brazilian Cerrado are described and illustrated based on the adult females. A new monotypic genus, Cerradococcus Kondo, Pacheco da Silva & Peronti, gen. nov., is erected to accommodate Cerradococcus gillianwatsonae Kondo, Pacheco da Silva & Peronti, sp. nov., found on leaves of Didymopanax vinosus (Cham. & Schltdl.) Marchal (Araliaceae). In addition, a new species of Philephedra Cockerell, 1898, Philephedra paralutea Kondo & Pacheco da Silva, sp. nov., found on an undetermined host plant, is described. Philephedra zipolitana Gavrilov-Zimin, 2023 is sunk as a junior synonym of Philephedra parvula (Cockerell, 1899), syn. nov. A diagnosis for the genus Philephedra and an updated key to species in the genus are also provided.